How relevant is job mismatch for German graduates? - Francesco Berlingieri; Daniel Erdsiek (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
In this study, we examine the incidence and direct consequences of job mismatch for German graduates. Beyond measuring job mismatch by the comparison of qualification obtained by employees and required for a job, we employ self-reported skill mismatch variables concerning overall skills and more detailed information about the surplus or deficit in specific competences. The results indicate that a substantial share of graduates underutilizes own skills in the job. The rate of overqualification and skill mismatch is found to differ strongly between fields of study, type of university and gender. In addition, we investigate to what extent jobs of matched graduates differ from jobs held by mismatched graduates. Jobs of the latter are found to exhibit lower complexity and creativity requirements but to be more monotone than matching jobs. Furthermore, we provide a conceptual underpinning of the possible explanations of job-worker mismatch and its implication for different actors in the economy.
urn:nbn:de:bsz:180-madoc-326692
Keywords: J24; I2; 330; job mismatch; overqualification; skill mismatch; Matching; Unterbeschäftigung; Deutschland